Aquatic insects along environmental gradients in a karst river system: A comparative analysis of EPT larvae assemblage components. Issue 3 (24th March 2014) - Hrovat, Mojca; Urbanič, Gorazd; Sivec, Ignac
<x xml:space="preserve">Abstract</x> Studying the response of assemblages either to natural or human induced environmental gradients is challenging due to spatial and temporal heterogeneity in river systems. This study identified the relationship between environmental variables, as well as sampling date, and Ephemeroptera (E), Plecoptera (P), Trichoptera (T) assemblages in a karst river system. Each assemblage component (E, P, T, EP, ET, PT, and EPT) is analyzed separately. Ten direct influential variables (water depth, water temperature, current velocity, dissolved oxygen concentration, oxygen saturation, pH, nitrate concentration, total solids, and total suspended solids) and sampling date were considered in order to identify environmental gradients after removal of the effect of stream size and habitat heterogeneity; both parameters were used as covariables. Thus, the observed effects of selected 10 variables were those that were not explained also by Strahler stream order and habitat heterogeneity. Examination of the EPT assemblage characteristics using the non‐parametric Kruskal–Wallis test showed significant spatial variations in richness/diversity metrics (number of EPT taxa, Shannon–Wiener diversity) but not in functional metrics (Gatherers/Collectors, Grazers, and Scrapers). The temporal variation in all metrics was substantial. Assemblage variances (R2) and adjusted assemblage variances (R2adj) of >35% and >20%, respectively, were obtained. Main environmental gradients representing hydrogeology and eutrophication as well as hydraulic and oxygen gradient for EPT assemblages were recognized. It appears that eutrophication is the key ecological factor for most assemblage components in a Dinaric karst river system, although Plecoptera assemblages were best explained by temperature regime and oxygen conditions. This study suggests that a variation in the diversity between E, P, and T taxa influences an assemblage–environment relationship. Environmental variables that were best predictors for assemblages with more than one insect group were associated with assemblages with high diversity. This study provides methods and approaches to recognize the main factors determining biotic assemblages' structures in Dinaric karst river systems and thus provides a basis to develop appropriate biodiversity conservation policies.